Short-term and multi-state reliability model for an industrial gas turbine - Lemma, T.A. (Asian Research Publishing Network, 2016)
This paper presents a short-term, multi-state reliability model for an industrial gas turbine. A new method is introduced to define the state boundaries. The transition intensities between any two states are determined from actual operation data and a Markov chain embedded in the operation data. The Chapman Kolomogorov equation corresponding to N-states is given. The equation can be applied to any gas turbine system. In the current paper, it is applied to a power plant having two identical 5.2 MW (nominal capacity at ISO condition) Siemens Taurus 60S gas turbines. The specific model included droop and isochronous modes of operation. The results show that the forced outage rates for the two gas turbines converge to 0.513 and 0.2661, respectively, when tââ. Such a model will be applicable for short term planning of the operation of gas turbines hence contributing to a saving in life-cycle or maintenance cost. Â© 2006-2016 Asian Research Publishing Network (ARPN).